Cultural Dimensions of Trade Fairs: A Longitudinal Analysis of Urban Development and Destination Loyalty in Thessaloniki - Dimitris Kourkouridis; Asimenia Salepaki (Urban Science, 2025)
Trade fairs are not only commercial platforms but also catalysts for urban development, city branding, and international engagement. This longitudinal study analyzes data from trade fair exhibitors from China, the United Arab Emirates (UAE), and Germany to examine how cultural differences influence their experiences, satisfaction, and destination loyalty within the urban landscape of Thessaloniki. By adopting Social Exchange Theory (S.E.T.) as a framework, this research applies a mixed-methods approach, combining surveys and in-depth interviews conducted over multiple years (2017–2024) at the 82nd, 86th, and 88th Thessaloniki International Fair (T.I.F.). The empirical material consists of 226 survey responses (116 from China, 44 from the UAE, and 84 from Germany) and 52 semi-structured interviews, analyzed using descriptive and non-parametric statistics, alongside thematic interpretation of qualitative data. Findings reveal distinct exhibitor expectations. These cultural distinctions shape their perceptions of Thessaloniki’s infrastructure, services, and overall urban experience, influencing their likelihood to revisit or recommend the city. This study underscores the long-term role of trade fairs in shaping urban economies and offers insights into how cities can leverage international exhibitions for sustainable urban growth. Policy recommendations highlight the need for tailored infrastructural improvements, strategic city branding initiatives, and cultural adaptations to enhance exhibitor engagement and maximize the economic impact of global events.